Pelatihan Memaksimalkan Profit Penjualan Produk Abon Gulung Hawai Bakery Menggunakan POM-QM - Tirsa Ninia Lina; Matheus Supriyanto Rumetna; Wiesje Ferdinandus; Frety Matahelumual (Yayasan Literasi Sains Indonesia, 2023)
Hawaii Bakery sells culinary products that are much loved by people in the archipelago region of Papua, Indonesia. The product is rolled shredded bread, which is the mainstay product of Hawaii Bakery. The current situation and conditions experienced by Hawaii Bakery are deemed necessary for adjustment, given that the main problem faced is maximizing profits with limited shipping costs and selling prices that must be adjusted. This provides an opportunity for the Sorong University of Victory Community Service (PkM) team to conduct a PkM program in the form of training using the POM-QM software for Windows. This training is to share knowledge and also help Hawaii Bakery to innovate and maintain business activities. The main thing is how Hawaii Bakery can maximize profit. After evaluating all the steps for implementing the Community Service Program, an average value of 95% is obtained for the increase in partner understanding. The 95% figure shows that the PkM implementation carried out by the Victory University Sorong University PkM team was very successful. This is a motivation for the team to continue to do the same thing and even improve the performance of the PkM team in the future.